HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKUTENTANG GIZI SEIMBANG DENGAN STATUS GIZI SISWA KELAS IV DAN V DI SDIT NURUL FIKRI KOTA DEPOKPADA TAHUN 2019 - Dodi Saputra (2019)
Good nutrition status is important for the growth and development of elementary school children. Some factors that affect nutrition status are knowledge, attitude, and behaviour about nutrition balance. SDIT Nurul Fikri Depok is a private school in Depok, West Java. It was one of the provinces with nutrition problems. Based on nutrition status, IMT/U West Java has a prevalence of 24,4% for lean category and 18,4% for fat category in 2010. The research was to determine a correlation between knowledge, attitude, and behaviour about nutrition balance with nutrition status of the elementary school students. The research method used analytical studies, with a cross-sectional study design. The subjects were 99 students include students in grade IV and V. Primary data was taken using questionnaire. Category of respondents nutrition status was determined based on body mass index/age. It was obtained the percentage of male respondents 47,5%, female 52,5%, aged nine 25,3%, aged ten 45,5%, aged eleven 29,3%. The result of data analysis there ware correlation between knowledge with nutrition status (p=0,046;OR=2,381;95%CI=1,109-7,224),attitude with nutrition status (p=0,014;OR=6,700;95%CI=1,220-36,784), and behaviour with nutrition status (p=0,041;OR=2,115;95%CI=0,827-5,409).There were a correlation between knowledge, attitude, and behaviour about nutrition balance with nutrition status on students of SDIT Nurul Fikri Depok.